Māori Law and Hart: A Brief Analysis - Stephens, Māmari (Victoria University of Wellington Law Review, 2001)
This is an edited version of a seminar paper presented in the context of the LLB(Hons) programme. It provides a contemporary perspective of Maori law from the standpoint of HLA Hart's theory of the union of primary and secondary rules.